Volatile snowlines in embedded disks around low-mass protostars - Harsono, Daniel; Bruderer, Simon; Dishoeck, Ewine F. van (Astronomy and astrophysics, 2015)
Context. Models of the young solar nebula assume a hot initial disk in which most volatiles are in the gas phase. Water emission arising from within 50 AU radius has been detected around low-mass embedded young stellar objects. The question remains whether an actively accreting disk is warm enough to have gas-phase water up to 50 AU radius. No detailed studies have yet been performed on the extent of snowlines in an accreting disk embedded in a dense envelope (stage 0). Aims. We aim to quantify the location of gas-phase volatiles in the inner envelope and disk system for an actively accreting embedded disk.Methods. Two-dimensional physical and radiative transfer models were used to calculate the temperature structure of embedded protostellar systems. Heating due to viscous accretion was added through the diffusion approximation. Gas and ice abundances of H2O, CO2, and CO were calculated using the density-dependent thermal desorption formulation. Results. The midplane water snowline increases from 3 to ~55 AU for accretion rates through the disk onto the star between 10-9-10-4M⊙ yr-1. CO2 can remain in the solid phase within the disk for Ṁ ≤ 10-5M⊙ yr-1 down to ~20 AU. Most of the CO is in the gas phase within an actively accreting disk independent of disk properties and accretion rate. The predicted optically thin water isotopolog emission is consistent with the detected H218O emission toward the stage 0 embedded young stellar objects, originating from both the disk and the warm inner envelope (hot core). An accreting embedded disk can only account for water emission arising from R< 50 AU, however, and the extent rapidly decreases for Ṁ ≤ 10-5M⊙ yr-1. Thus, the radial extent of the emission can be measured with future ALMA observations and compared to this 50 AU limit. Conclusions. Volatiles such as H2O, CO2, CO, and the associated complex organics sublimate out to 50 AU in the midplane of young disks and, thus, can reset the chemical content inherited from the envelope in periods of high accretion rates (>10-5M⊙ yr-1). A hot young solar nebula out to 30 AU can only have occurred during the deeply embedded stage 0, not during the T Tauri phase of our early solar system.
Gesehen am 13.07.2020